2021
DOI: 10.3390/nu13072159
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fibre Intervention for Gut Microbiota, Sleep, and Mental Health in Adults with Irritable Bowel Syndrome: A Scoping Review

Abstract: Irritable bowel syndrome (IBS) is a common functional gastrointestinal disorder affecting 4–5% of the global population. This disorder is associated with gut microbiota, diet, sleep, and mental health. This scoping review therefore aims to map existing research that has administrated fibre-related dietary intervention to IBS individuals and reported outcomes on at least two of the three following themes: gut microbiota, sleep, and mental health. Five digital databases were searched to identify and select paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 128 publications
(176 reference statements)
0
9
0
Order By: Relevance
“…Of note, the only study in adult humans was conducted in Asian people [11]. As diet is a main factor impacting on the composition of gut microbiome [8,13], these findings cannot be necessarily translated to a Western population.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the only study in adult humans was conducted in Asian people [11]. As diet is a main factor impacting on the composition of gut microbiome [8,13], these findings cannot be necessarily translated to a Western population.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, intestinal bacteria account for approximately 98% of the total microbial community, whereas the rest contains fungi (0.1%), viruses and protozoa [ 7 9 ]. The stabilized gut microbiota is required for various complex physiological and metabolic processes, whereas gut microbial dysbiosis may result in multiple gastrointestinal diseases including diarrhea, enteritis and irritable bowel syndrome [ 10 , 11 ]. Although these microbes colonize the intestine, they may result in systemic effects [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between dietary fiber intake and phthalates exposure is still unknown. Some previous studies suggested that high DDIF was negatively associated with sleep trouble ( 21 , 22 ). One previous study showed that high DDIF could regulate the hormone concentrations in women ( 23 ).…”
Section: Discussionmentioning
confidence: 96%